Maternal vitamin B12 during pregnancy and schizophrenia in offspring - Sourander, Andre; Silwal, Sanju; Surcel, Heljä-Marja; Hinkka-Yli-Salomäki, Susanna; Cheslack-Postava, Keely; Upadhyaya, Subina; McKeague, Ian W.; Brown, Alan S. (Elsevier, 2025)
Background
Maternal nutritional deficiency is linked with several adverse outcomes in offspring but the link between maternal vitamin B12 levels and offspring schizophrenia remains unexplored.
Methods
In this nationwide population-based nested case-control design, 1145 schizophrenia cases were born between 1987-1997 and diagnosed by 2017 and each case were matched with a control. Maternal vitamin B12 levels during the first and early second trimesters of pregnancy were measured using chemiluminescence microparticle immunoassay from maternal sera. Conditional logistic regression was used to examine the association between maternal vitamin B12 levels and offspring schizophrenia.
Results
Low maternal vitamin B12 levels were not associated with offspring schizophrenia in unadjusted (OR 1.04, 95% CI 0.88-1.24) or adjusted analyses (aOR 1.14, 95% CI 0.95-1.37). When analyzed by quintiles, no significant association was observed between the lowest versus highest quintile of maternal vitamin B12 levels and schizophrenia in unadjusted (OR 1.01, 95% CI 0.78-1.30) or adjusted analyses (OR 0.89, 95% CI 0.68-1.17).
Conclusion
Maternal vitamin B12 levels in early pregnancy were not associated with offspring schizophrenia. Future studies measuring both genetic and environmental factors are required to elucidate the role of maternal vitamin B12 deficiency in schizophrenia and its potential pathways to influence schizophrenia in offspring.